2011
DOI: 10.1007/s00221-011-2607-1
|View full text |Cite
|
Sign up to set email alerts
|

Repetitive common peroneal nerve stimulation increases ankle dorsiflexor motor evoked potentials in incomplete spinal cord lesions

Abstract: Plasticity of corticospinal tract (CST) activity likely plays a key role in motor function recovery after central nervous system (CNS) lesions. In non-injured adults, 30 min of repetitive common peroneal nerve stimulation (rCPnS) increases CST excitability by 40-50% and the effect persists for at least 30 min. The present study evaluated with transcranial magnetic stimulation (TMS) the changes in CST excitability after 30 min of rCPnS in people with foot drop due to incomplete SCI. Suprathreshold rCPnS (25 Hz,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
41
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 27 publications
(44 citation statements)
references
References 64 publications
2
41
1
Order By: Relevance
“…Some studies have shown that patterned stimulation alone, comparable with what was used in the RS group, can improve corticospinal excitability, which in turn is linked to enabling rehabilitation in patients with SCI [28][29][30]32]. The present study demonstrates that coordinating FES with treadmill training in animals with SCI leads to better functional outcome than FES alone.…”
Section: Implications For Advancing Gait Rehabilitationsupporting
confidence: 57%
See 4 more Smart Citations
“…Some studies have shown that patterned stimulation alone, comparable with what was used in the RS group, can improve corticospinal excitability, which in turn is linked to enabling rehabilitation in patients with SCI [28][29][30]32]. The present study demonstrates that coordinating FES with treadmill training in animals with SCI leads to better functional outcome than FES alone.…”
Section: Implications For Advancing Gait Rehabilitationsupporting
confidence: 57%
“…There is evidence that patterned stimulation alone, i.e., not timed with afferent feedback, was sufficient to induce short-term plasticity in the spinal circuitry [29][30]62]. A single session of FES of the CPN was sufficient to enhance excitation in the corticospinal pathways controlling the TA in nondisabled subjects [30] and subjects with SCI [29].…”
Section: Possible Influence Of Fes+rtt On Spinal Circuitrymentioning
confidence: 99%
See 3 more Smart Citations